2009
DOI: 10.1007/s11121-009-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Influence of Demographic and Risk Factors on Difficult Child Behaviors

Abstract: This descriptive study examined the distribution of risk factors in a sample that was selected on the basis of existing potential for difficult child behaviors. We inquired into whether exposure to risk factors was distributed equally across different contexts of ethnicity, locality, and child gender. Participants included 731 mother-child dyads recruited from WIC Programs in rural, suburban, and urban localities. Cumulative risk indices were constructed using neighborhood, family, and individual risk factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…When distortion in the caregiver"s ratings were controlled for in the regression analysis, only race and distortion remained statistically significant although parenting stress, comfort in parenting, and appraisal of behavior were approaching significance. These findings were similar to a study of 731 mother-child dyads recruited from WIC Programs in rural, suburban, and urban localities (Wilson, Hurtt, Shaw, Dishion, & Gardner, 2009). In their study, even though the African American children were exposed to a greater number of risk factors and cumulative risk (poverty, violence, etc) in relation to other ethnic children and localities, they were not at greater risk for behavioral problems; Caucasian children had the highest risk.…”
Section: Level Of Risk Of Having a Child With A Behavioral Problemsupporting
confidence: 87%
See 1 more Smart Citation
“…When distortion in the caregiver"s ratings were controlled for in the regression analysis, only race and distortion remained statistically significant although parenting stress, comfort in parenting, and appraisal of behavior were approaching significance. These findings were similar to a study of 731 mother-child dyads recruited from WIC Programs in rural, suburban, and urban localities (Wilson, Hurtt, Shaw, Dishion, & Gardner, 2009). In their study, even though the African American children were exposed to a greater number of risk factors and cumulative risk (poverty, violence, etc) in relation to other ethnic children and localities, they were not at greater risk for behavioral problems; Caucasian children had the highest risk.…”
Section: Level Of Risk Of Having a Child With A Behavioral Problemsupporting
confidence: 87%
“…The authors of the study checked for differences in the perceptions of behavior problems between African American parents and Caucasian parents and found none. African American children were at lower risk of having a behavioral problem in spite of having the highest number of risk factors (Wilson et al, 2009). This has been supported by other researchers (Jaffee et al, 2005;Kendall et al, 2005).…”
Section: Level Of Risk Of Having a Child With A Behavioral Problemsupporting
confidence: 59%
“…For example, Brody and Flor (1998) have suggested that African American parents often use no-nonsense parenting strategies that include harsh reprimands and physical punishment along with positive affect. Moreover, research has shown that certain ethnic groups report greater exposure to environmental and individual risk factors than others yet demonstrate equal or lower levels of vulnerability to risk or morbidity (Ackerman, Kogos, Youngstrom, Schoff, & Izard, 1999; Bluestone & Tamis-LeMonda, 1999; Wallace & Muroff, 2002; Wilson, Hurtt, Shaw, Dishion, & Gardner, 2007). Hence, this study underscores the importance of addressing ethnic differences in positive parenting practices by exploring positive behavior support in relation to other aspects of parenting (e.g., Ispa et al, 2004) and by understanding the impact of environmental risk on parenting (e.g., Wilson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that African American children, especially those from urban settings, experience a higher number of total risk factors in comparison to African Americans in other settings (i.e., suburban, rural), and in comparison to children from other racial minority groups (Wilson, Hurtt, Shaw, Dishion, & Gardner, 2009). This finding is particularly relevant to the present study because research suggests that the accumulation of multiple risk factors, more than the presence of a single risk factor, predicts later problems (Evans, Li, & Whipple, 2013).…”
mentioning
confidence: 99%